(untitled) (CIPEEX, 2022)
NECROPSY IS A MEDICAL PROCEDURE THAT CONSISTS OF EXAMINING A CORPSE TO DETERMINE THE CAUSE AND MODE OF DEATH AND EVALUATING ANY DISEASE OR INJURY THAT MAY BE PRESENT. IMPORTANCE, WHEN INDICATED AND PERFORMED IN THE RIGHT WAY, INVOLVES SEVERAL POSITIVE POINTS, SUCH AS PROVIDING TEACHING AND STUDY MATERIALS; DATA SOURCE FOR THE SECRETARIAT OF HEALTH AND EPIDEMIOLOGY; CLARIFY CASES WITHOUT CLINICAL DIAGNOSIS, AMONG SEVERAL OTHER FUNCTIONS. THERE ARE SOME CASES THAT ARE MANDATORY FOR NECROPSY, AND THE INDICATIONS SHOULD BE UNDERSTOOD BY PROFESSIONALS AND STUDENTS OF THE MEDICAL COURSE. IF SUCH INDICATIONS ARE NOT KNOWN AND OCCUR IN AN ERRONEOUS WAY, IT IS POSSIBLE TO INCUR INSTITUTIONALIZATION, SUFFERING ON THE PART OF THE FAMILY OF THE DECEASED, AMONG MANY OTHER BURDENS. THIS WORK AIMS TO ANALYZE THE UNDERSTANDING OF THE STUDENTS FROM THE FIRST TO THE EIGHTH PERIOD OF MEDICINE OF UNIEVANGLICA ON INDICATIONS OF NECROPSY. THIS IS A CROSS-SECTIONAL, QUANTITATIVE STUDY IN WHICH A MULTIPLE-CHOICE QUESTIONNAIRE ON NECROPSY INDICATIONS WILL BE APPLIED. THE DATA WILL BE ANALYZED, AND IT IS EXPECTED TO OBTAIN AN ESTIMATE OF THE DEGREE OF KNOWLEDGE ABOUT THE UNDERSTANDING OF MEDICAL STUDENTS FROM UNIEVANGLICA FROM THE FIRST TO THE EIGHTH PERIOD ON INDICATIONS OF NECROPSY. IN ADDITION, IT IS EXPECTED TO MAKE A COMPARISON OF THIS KNOWLEDGE BETWEEN THE PERIODS OF THE MEDICAL COURSE, FROM THE 1ST TO THE 8TH, AND TO DRAW A PROFILE OF EDUCATION IN THIS AREA IN EACH PERIOD.